2021
DOI: 10.1021/acsaelm.1c00511
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Annealing Temperature and Applied Electric Field on the Reliability of TiN/Hf0.5Zr0.5O2/TiN Capacitors

Abstract: The retention and endurance properties of TiN/Hf0.5Zr0.5O2/TiN ferroelectric memory capacitors are systematically investigated for their dependence on the temperature of the postmetallization annealing applied for the Hf0.5Zr0.5O2 crystallization and applied electric field. The increase of the annealing temperature from 400 to 600 °C affects the retention loss behavior dramatically, inducing the valuable retention improvement. A simultaneous decrease of the imprint shift indicates the primary role of imprint i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The advantage of HZO over other perovskite ferroelectric materials and Sidoped hafnium oxides (HSO) has been mentioned in previous reports, which involves ease of deposition by the ALD process, scalability to thin film, and lower process temperature (Muller et al, 2012;Jerry et al, 2017;Kim H. et al, 2018;Ali et al, 2019;Ni et al, 2019;Cheema et al, 2020). Recent reports have also shown that low process temperature, superior interface quality, and reducing the numbers of defect sites in HZO improve the endurance of the HZO-based transistors (Dutta et al, 2020;De et al, 2021a;De et al, 2021b;Khakimov et al, 2021). Apart from the device structure, low process temperature and interface properties, the pulse scheme, and bias-technique during the WRITE operation also play an important role in determining the WRITE-endurance limit of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of HZO over other perovskite ferroelectric materials and Sidoped hafnium oxides (HSO) has been mentioned in previous reports, which involves ease of deposition by the ALD process, scalability to thin film, and lower process temperature (Muller et al, 2012;Jerry et al, 2017;Kim H. et al, 2018;Ali et al, 2019;Ni et al, 2019;Cheema et al, 2020). Recent reports have also shown that low process temperature, superior interface quality, and reducing the numbers of defect sites in HZO improve the endurance of the HZO-based transistors (Dutta et al, 2020;De et al, 2021a;De et al, 2021b;Khakimov et al, 2021). Apart from the device structure, low process temperature and interface properties, the pulse scheme, and bias-technique during the WRITE operation also play an important role in determining the WRITE-endurance limit of the device.…”
Section: Introductionmentioning
confidence: 99%
“…V 0 act as the domain pinning centers and could be relaxed upon field cycling, consequently resulting in a higher P r . Typically a larger amount of V 0 would correlate to a more pronounced wake-up effect and the amount of V 0 in HZO would increase with annealing temperature. , Therefore, it can be inferred that more significant wake-up effect is expected as the annealing temperature increases. However, the wake-up effect becomes even insignificant with the annealing temperature in this study, implying another mechanism behind the wake-up effect we observed.…”
Section: Resultsmentioning
confidence: 99%
“…Retention, in general, is a complex problem for HfO 2 -based capacitors, since a common benchmark of 10 years at 85 °C appears to be difficult to achieve, especially at the BEOL-compatible annealing temperatures . For this reason, finding a way to improve retention without elevation of the annealing temperature is an important task.…”
Section: Introductionmentioning
confidence: 99%